Designing the corrosion products of ZnAl15: a new approach to smart corrosion protection coatings?. (15th July 2019) - Bobzin, Kirsten; Öte, Mehmet; Knoch, Martin Andreas
Highlights: β-ZnAl15 can be produced by Thermal Spray and Melt-Spinning. β-ZnAl15 favours the formation of a homogenous LDH layer in a salt spray test. α-η-ZnAl15 results in inhomogeneous corrosion in a salt spray test. A reaction of LDH to simonkolleite is indicated. Abstract: ZnAl coatings are known to provide reliable corrosion protection for low-grade structural steels in most environments. Depending on the coating process, different phase compositions can be observed in such coatings. In case of thermal spraying, the high cooling rates were proven to result in the formation of metastable β-ZnAl for the first time in literature. To assess the influence on the corrosion behaviour, β-ZnAl and α-η-ZnAl samples were produced and corroded in a salt spray test. A pronounced influence of the phase composition on the formation of layered double hydroxides was observed.